Construction of Ideological and Political Mixed Teaching in Higher Education under the Digital Transformation - Liang, Shidong; Zhang, Yinan; Ma, Minghui; He, Jianjia; He, Shengxue (International Journal for Innovation Education and Research, 2023)
This article focuses on the current demands for reform in ideological and political education in higher education, within the context of the digital information and communication era. Specifically, it proposes a plan for integrating ideological and political education into higher education courses using the widely-used blended learning mode in a digitally transformed environment. This plan aims to leverage digital teaching methods, such as the development of multimedia courseware, to enrich classroom teaching content, increase student engagement and learning outcomes, deepen students' understanding and awareness, and enable them to effectively absorb a wealth of information in a limited time. By subtly linking the process of learning professional knowledge with their personal, social, and national development, this plan seeks to foster a professional education philosophy that cultivates "socialist successors."